Comparison of shear bond strength of metallic brackets bonded to ceramic surfaces utilizing different adhesive systems: An in vitro study - María Belén Paz Pulido; Pedro Mariano Pereira; Ricardo Pitschielller; Luis Proença; Iman Bugaighis (Journal of Orthodontic Science, 2023)
OBJECTIVE: To compare the shear bond strength (SBS) of orthodontic brackets bonded to three different types of ceramic surfaces (feldspathic, lithium disilicate, and zirconium) using Assure® Plus All and Transbond™ XT adhesives. MATERIALS AND METHODS: The sample comprised 72 monolithic computer-aided design and computer-aided manufacturing (CAD/CAM) ceramic samples that were randomly divided into six groups of 12 specimens each. Three groups (G1, feldspathic ceramic; G3, lithium disilicate ceramic; G5, zirconium surfaces) were bonded to metal brackets using Assure® Plus All adhesive, whereas the remaining three groups (G2, G4, G6; with the ceramic type in the same order as that in the previous groups) were bonded to metal brackets using Transbond™ XT. The samples were then subjected to 10,000 thermocycles. The SBS was calculated using the shear tests. The site of bonding failure was classified using the adhesive remnant index (ARI) score. One-way analysis of variance (ANOVA) and Kruskal–Wallis tests were used for statistical analyses at a 5% significance level. RESULTS: Statistically significant differences were observed in the mean SBS values of the groups (P < 0.001). The mean SBS for G6 (zirconium plus Transbond™ XT) (2.52 MPa) was significantly lower than that for all other groups. Furthermore, statistically significant differences were found in the ARI score distribution among the groups (P < 0.001). Differences were identified between G6 and G3 (lithium disilicate Plus All Assure® Plus All) and G5 (zirconium plus Assure® Plus All). CONCLUSIONS: The mean bonding strength of brackets with Assure® Plus All was higher than that with Transbond™ XT for all three types of ceramics. However, all groups, except the zirconium plus Transbond™ XT group, showed acceptable bonding strength for orthodontic purposes. The application of hydrofluoric acid followed by silane and finally the Assure® Plus All adhesive system is adequate for bonding brackets to any of the ceramic tested surfaces.